Α‐Dithiophene‐tetrathiafulvalene – a Detailed Study of an Electronic Donor and Its Derivatives. Issue 13 (1st March 2013) - Silva, Rafaela A. L.; Neves, Ana I.; Afonso, Mónica L.; Santos, Isabel C.; Lopes, Elsa B.; Del Pozo, Freddy; Pfattner, Raphael; Mas‐Torrent, Marta; Rovira, Concepció; Almeida, Manuel; Belo, Dulce
Abstract: The electronic donor α‐DT‐TTF (α‐dithiophene‐tetrathiafulvalene), which among the thiophenic TTF derivatives has remained essentially unexplored, and some of its charge transfer salts are described in detail in this paper. This donor was efficiently prepared by the homocoupling of 5, 6‐thieno[2, 3‐ d ]‐1, 3‐dithiol‐2‐one, and its redox properties are intermediate between those of DT‐TTF (dithiophene‐tetrathiafulvalene) and BET‐TTF [bis(ethylenethio)tetrathiafulvalene]. The crystal structure of α‐DT‐TTF shows a molecular packing composed of trios of donor chains with alternating orientation. This pattern is clearly distinct from those previously found in all other thiophenic TTF donors. Used as an active material in a field‐effect transistor, α‐DT‐TTF presents a mobility μ FE = 5 × 10 –5 cm 2 /V s. The possibility to convert this new donor to conducting charge‐transfer salts with suitable anions was demonstrated by preparing its PF6 – salts. Two salts with different crystal structures and stoichiometries were identified by X‐ray diffraction studies: (α‐DT‐TTF)(PF6 )0.6 and (α‐DT‐TTF)2 (PF6 ). The electrical conductivities of these salts, measured in the single crystal, range from 9 to 50 S/cm at room temperature. In all cases, the salts show a semiconducting behaviour and properties that are comparable to those of the analogous nonaromatic BET‐TTF salts. Abstract : α‐DT‐TTF (α‐dithiophene‐tetrathiafulvalene), a new thiophene TTF electronic donor is reported. Its synthesis and characterization opens the way to the preparation of a new series of charge‐transfer salts. The first member of this family is the salt with the PF6 – anion, which shows a σ r.t. value of 46 S/cm and properties comparable to those of the BET‐TTF [bis(ethylenethio)tetrathiafulvalene] analogue.